Protein localization by fluorescence microscopy : a practical approach - Allan, Victoria J. (Practical approach series ;, 2000)
There is an ever-increasing number of genes that have been sequenced but are of completely unknown function. The ability to determine the location of such gene products within the cell, either by the use of antibodies or by the production of chimeras with green fluorescent protein, is a vital step towards understanding what they do. This is one major reason why fluorescence microscopy is enjoying a revival. This no-nonsense guide provides detailed, practical advice on all aspects of the subject: from choosing the right equipment, to interpreting results. It balances the advantages of a wide range of techniques - including live cell work - against the potential pitfalls, offering invaluable "tricks of the trade" along the way. Protein Localization by Fluorescence Light Microscopy: A Practical Approach has something to offer all microscopists, giving a solid grounding to the novice whilst extending the range of the experienced user